Digital Mapping the Evolution of Green Human Resource Management: A Bibliometric Analysis Using Biblioshiny - Augustin Patrick; Hardiman Sudirman; Marwa Mohammed Ahmed; Femi Asteriniah; Arif Rahman Hakim; Darwish Khan Tahiry (International Journal of Educational Administration, Management, and Leadership, 2025)
Green Human Resource Management has become an important research topic as organizations increasingly integrate environmental sustainability into human resource practices. This study aims to map the development of Green HRM research using bibliometric analysis. Bibliographic data were collected from the Scopus database using the keywords “green human resource management” OR “green HRM.” After applying filters related to publication year, document type, language, source type, and publication stage, 1,031 journal articles published between 2019 and 2025 were included in the final dataset. The data were analyzed using Biblioshiny, the web-based interface of the bibliometrix package in RStudio. The findings show that Green HRM research has grown rapidly, with an annual growth rate of 43.89%. The dataset involved 2,913 authors, with an international co-authorship rate of 44.62%, indicating strong scholarly collaboration. The most productive source was Sustainability (Switzerland), while the most productive countries included China, Pakistan, Malaysia, India, and Indonesia. Keyword analysis shows that the field is mainly centered on green human resource management, environmental performance, sustainability, green innovation, and sustainable performance. The thematic map and co-occurrence network indicate that Green HRM research has evolved toward more specific themes related to employee green behavior, sustainability performance, green training, employee engagement, and environmental outcomes. This study contributes to the literature by providing a comprehensive bibliometric overview of Green HRM research and identifying future research directions related to sustainability-oriented HR practices, green innovation, employee behavior, and organizational environmental performance.